Materials Informatics 2019
DOI: 10.1002/9783527802265.ch7
|View full text |Cite
|
Sign up to set email alerts
|

Automated Computation of Materials Properties

Abstract: Materials informatics offers a promising pathway towards rational materials design, replacing the current trial-and-error approach and accelerating the development of new functional materials. Through the use of sophisticated data analysis techniques, underlying property trends can be identified, facilitating the formulation of new design rules. Such methods require large sets of consistently generated, programmatically accessible materials data. Computational materials design frameworks using standardized par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 233 publications
(329 reference statements)
0
2
0
Order By: Relevance
“…the optimization of materials and process parameters (see e.g. [3][4][5][6]). In the field of fusion plasma, several studies applying ML to a plasma ion source were reported [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…the optimization of materials and process parameters (see e.g. [3][4][5][6]). In the field of fusion plasma, several studies applying ML to a plasma ion source were reported [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In the years since our previous work was published there has been increasing interest in the generation and use of generalized k-point grids [6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Of particular note, Hart and co-workers have recently developed algorithms and released an open-source software package (GRkgridgen) for generating generalized k-point grids on the fly [27,28].…”
Section: Introductionmentioning
confidence: 99%